THE PROPERTIES OF ENERGY-COUPLING FACTOR TRANSPORTER COMPLEX WITH THE NANOBODIES - Ramdhan Anshari, Zaid
ATP-binding cassette (The ABC) proteins serve many functions, including the transport of nutrients into the cell, transport of compounds across organellar membranes, the secretion of proteins, antigen (peptide) presentation, cell volume regulation. regul ation of protein synthesis, detoxifaction and antibiotic resistance. Energy-coupling factor (ECF) transporter arc a group of ATP-binding cassette transporters responsible for micronutrients transport in prokaryotes. ECF transporters consist of two proteins in cystoplasm and two membrane proteins in lipid bilayer. The hypothetical mechanism of ECF transporter was defined. To obtain the complete mechanism of ECF transporter we need to define the structure of ECF transporter in many states.